Media and Communication Cells in Algerian Universities "A Critical Look and Future Visions" - Goudjil , Nor El Abidine; Kouadri, Lokmane (International Journal of Social Communication, 2025)
Media and communication cells in the Algerian university are considered a vital element and a key player in building relationships and enhancing communication inside and outside the university institution. They work to provide effective channels of communication with students, professors and employees on the one hand, and with the external environment of the university on the other, which contributes to enhancing transparency and building the confidence of the community as a whole in the university, and plays a major role in building a positive image of the university and highlighting its activities at various levels. Through this intervention, we seek to shed light on the reality of communication and media cells in Algerian universities and the challenges they face, whether in the field of providing information quickly and transparently, or in the field of training human cadres working in them, as well as their efficiency in managing crises, dealing with the media and improving the image of the institution